Application of UAT (User Acceptance Test) Evaluation Model in Minggon E-Meeting Software Development - Bayu Priyatna; April Lia Hananto; Muhammad Nova (Universitas Singaperbangsa Karawang, 2020)
The Sunday e-meeting application is an android application for controlling the results of a meeting which is an official face-to-face agenda activity carried out by two or more people with the aim of discussing a problem, finding a way out and making decisions in order to achieve individual or organizational goals. E-meeting is one solution to the problems contained in manual meetings. However, the system that has been built has not yet been evaluated so that the e-meeting system is not yet known whether it can be an effective and efficient system. The method used in the evaluation of this system uses the UAT (User Acceptance Test). The results of the evaluation of the system were different percentages, first in terms of design 45% of respondents answered that they did not agree with the appearance of the e-meeting system, then in terms of convenience 79.56% of respondents answered agreed with the use of the e-meeting system. facilitate the process of scheduling and setting the meeting time, and in terms of efficiency 85.47% of respondents answered that they strongly agree that this system will speed up the response of citizens to find out the schedule of meetings and meeting activities can be recapitulated automatically. So it can be concluded that the e-meeting system is acceptable and has good convenience, design and efficiency.